2019
DOI: 10.1212/wnl.0000000000008318
|View full text |Cite
|
Sign up to set email alerts
|

Tissue bridges predict recovery after traumatic and ischemic thoracic spinal cord injury

Abstract: ObjectiveTo investigate the spatiotemporal evolution and predictive properties of intramedullary damage and midsagittal tissue bridges at the epicenter of a thoracic spinal cord injury (SCI) using MRI.MethodsWe retrospectively assessed midsagittal T2-weighted scans from 25 patients with thoracic SCI (14 traumatic, 11 ischemic) at 1 month post-SCI. In 12 patients with SCI, linear mixed-effects models on serial MRI explored temporal trajectories of quantifiable lesion markers (area, length, and width) and tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 43 publications
(62 reference statements)
0
55
0
Order By: Relevance
“…Tissue bridge data from a small subset of the study population was previously reported in a different context. [9][10][11]…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Tissue bridge data from a small subset of the study population was previously reported in a different context. [9][10][11]…”
Section: Experimental Designmentioning
confidence: 99%
“…7 8 Preserved tissue bridges adjacent to the intramedullary lesion cavity, which can be identified in all patients with incomplete SCI, 9 are permissive for electrophysiological information flow and the size of which is predictive of functional recovery. [9][10][11] Importantly, NP below the level of injury develops over time. 12 This suggests that fractions of sensory pathways within preserved tissue bridges become active over time and may affect both ascending and descending modulatory systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to stimulated pericyte and collagen treatment, pericyte‐treated males and females produced neurofilament that spanned the wounded area (Figure 5). Similarly, tissue bridges across the wounded area have been associated with improved recovery after SCI in humans 50 . The rescue of neurofilament density as compared to controls and maintenance of blood flow perfusion in female rats injected with stimulated pericytes, however, did not lead to functional motor recovery in the current study.…”
Section: Discussionmentioning
confidence: 46%
“…After SCI, the limited regenerative capacity of the adult mammalian spinal cord has been attributed to the formation of cavities and glial scars that interrupt the ascending and descending pathways [17][18][19]. Now, NSC transplantation is considered an appropriate choice for treating SCI [20].…”
Section: Discussionmentioning
confidence: 99%